Central California foreshocks of the great 1857 earthquake - Sieh, Kerry (2013)
Analysis of contemporary accounts indicates that several small to moderate central California earthquakes preceded the great 1857 earthquake by 1 to 9 hr. The earliest events apparently were felt only in the San Francisco area or the Sacramento and Sierran Foothills region. Two later and much more widely felt foreshocks were experienced within the region bounded by San Francisco, Visalia, Fort Tejon, and Santa Barbara. A comparison with felt areas and intensity distributions of modern events of known source and magnitude indicates that these later two shocks were 5 ≦M ≲ 6 and probably originated at some point within an area of radius ≈60 km that includes the southeastern 100 km of the historically creeping segment of the San Andreas fault. The northwestern terminus of the 1857 rupture is probably located along this segment.